THE IMPORTANCE OF PARTICIPATORY STRATEGIC PLANS IN MUNICIPALITY FEDERATIONS: CASE OF THE METROPOLITAN FEDERATION OF MUNICIPALITIES (FEMETROM) - Gamboa Conejo, Rita (2012)
This paperis focused on the importance of preparing participatory strategic plans for municipalityfederations as a tool to help them visualize their future and develop in the presentthe actions necessaryto achieve it. For a better understanding of this proposal,strategic planning is analyzed as a fundamental process in organizations. The municipal system in Costa Rica is mentioned, as well as the formation of municipal federations.Planning is also related to the actions performed by such federations. Finally, a case study is presented using a strategic plan prepared for the Metropolitan Federation of Municipalities(FEMETROM) in 2010.